Establishment of Reference Intervals for Alkaline Phosphatase in Pakistani Children Using a Data Mining Approach - Ahmed, Sibtain; Zierk, Jakob; Khan, Aysha Habib (Labmedicine, 2019)
OBJECTIVE: To establish reference intervals (RIs) for alkaline phosphatase (ALP) levels in Pakistani children using an indirect data mining approach. METHODS: ALP levels analyzed on a Siemens Advia 1800 analyzer using the International Federation of Clinical Chemistry's photometric method for both inpatients and outpatients aged 1 to 17 years between January 2013 and December 2017, including patients from intensive care units and specialty units, were retrieved. RIs were calculated using a previously validated indirect algorithm developed by the German Society of Clinical Chemistry and Laboratory Medicine's Working Group on Guide Limits. RESULTS: From a total of 108,845 results, after the exclusion of patients with multiple specimens, RIs were calculated for 24,628 males and 18,083 females with stratification into fine-grained age groups. These RIs demonstrate the complex age- and sex-related ALP dynamics occurring during physiological development. CONCLUSION: The population-specific RIs serve to allow an accurate understanding of the fluctuations in analyte activity with increasing age and to support clinical decision making.
EVALuna2:210520